Comparison of Four Methods of Treating Ectopic Pregnancy: A Retrospective Cohort Study - Inal, Zeynep Ozturk; Inal, Hasan Ali (Geburtshilfe und Frauenheilkunde, 2018)
Objective To compare the results of expectant management, single and multidose methotrexate (MTX) and surgical management of ectopic pregnancy (EP).Materials and Methods In this retrospective cohort study, the original files of 233 patients who were treated for EP between May 2009 and December 2016 were analyzed. The patients were assigned to the following groups based on the applied treatment methods: Group 1, expectant management (n = 24), Group 2, single-dose MTX (n = 144), Group 3, multiple-dose MTX (n = 25), and Group 4, surgical intervention (n = 40). The following parameters were recorded and assessed: sociodemographic characteristics, pelvic ultrasonography findings (gestational sac, ectopic mass appearance, positive fetal cardiac activity), serum beta-human chorionic gonadotropin (β-hCG) levels on Day 0, Day 4, and Day 7, and surgical procedures in women that underwent surgical interventions.Results The sociodemographic characteristics were similar in all four groups. The percentage of ectopic mass and positive fetal cardiac activity was greater and the diameter of the mass was larger in Group 4 than in the other groups. The β-hCG values on Day 0, Day 4, and Day 7 were statistically different between the groups (p < 0.001). The cutoff value for the β-hCG change for EP resolution was 18% between Day 0 and Day 4 (AUC = 0.726, p < 0.001) and 15% between Day 4 and Day 7 (AUC = 0.874, p < 0.001). The probability of the requirement for an additional dose of MTX was 0.78 (95% CI 0.71 – 0.87; p < 0.001) times lower in patients who had a > 18% decrease in β-hCG levels from Day 0 to Day 4 in comparison to those who had a decrease < 18% from Day 0 to Day 4. The probability of the requirement for an additional dose of MTX was 1.64 (95% CI 1.25 – 2.16; p < 0.001) times greater in patients whose reduction in β-hCG levels from Day 4 to Day 7 was < 15% in comparison to those who had > 15% reduction from Day 4 to Day 7.Conclusions Additional dose requirements for patients with EP may be predicted early in the changes in β-hCG levels between Day 0 and Day 4. Further prospective studies are required to elucidate this issue.
Keywords: ectopic pregnancy; human chorionic gonadotropin; methotrexate; single dose; multiple dose; gynecology; infertility